Design Considerations for a Sub-mW Receiver Front-End for Internet-of-Things - Ehsan Kargaran; Danilo Manstretta; Rinaldo Castello (IEEE Open Journal of the Solid-State Circuits Society, 2021)
Internet-of-Things (IoT) and Wireless sensor networks (WSNs) require very low power transceivers. This paper presents techniques for minimizing power consumption of receiver (RX) frontends for short range wireless links. Two key approaches, i.e., current reuse and supply voltage reduction are compared. Different RX architectures such as direct-conversion, low-IF, sliding IF as well as phase-tracking RX, are compared, emphasizing their potential and limitations when targeting sub-mW RX power dissipation. Low-power design techniques for LNA, frequency generation blocks and baseband amplifiers are presented. As a case study, an efficient low-IF RX front-end for IoT is described in detail. In 28 nm CMOS, such a receiver occupies an active area of 0.1 mm2 and consumes only $350~{μ }\text{W}$ from a 0.9 V supply while showing a minimum in band NF of 6.2 dB. The achieved performance is very competitive with state-of-the-art ultra-low-power receivers, while consuming the lowest power.